Penggunaan Thariqah Mubasyarah sebagai Pembelajaran Bahasa Arab yang Efektif - Rahmah, Risa Rabiatur; Muzdalifah, Azizatul; Wijaya, Mu’alim; Ibrahim, Abdelrahman (Al Maghazi : Arabic Language in Higher Education, 2023)
Learning Arabic was part of the pesantren development program in Indonesia. The success of a study depends on the method used. The purpose of this research was to find out how far the mubasyarah congregation can be used for higher education. This research conducted through a literature review, collecting several empirical documents. The result indicated that the tarekat mubasyarah was a method of learning Arabic that did not use the mother tongue, Tariqah mubasyarah was a demonstration of language learning through tutukata, with an emphasis on mastery of mufrodat in everyday life. The active participation of teachers and students was an indication of successful learning. The purpose of this study was to determine the effectiveness of using Tariqoh Mubasyarah to overcome the low maharoh al Kalam in learning Arabic. Keywords: Direct Method, Higher Education, Learning Arabic